An Attempt to Develop the Tornado Impact Community Vulnerability Index (TICV): Measuring the Impact of Tornadoes on Community Vulnerability (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Tornado vulnerability relies upon the occurrence of and societal exposure to tornadoes for a specific area. Given the ongoing acknowledgment that physical procedures, yet social, political and monetary parts of hazards decide vulnerability and impact of an event, the following consistent advance would appear to be the improvement of arrangement systems that address those components. Arrangements for natural disasters, for example, the Fujita Scale for tornadoes and the Saffir-Simpson tropical storm scale, centre around the physical properties of the event, not the impact on a community. The objective of this research was to build up the Tornado Impact Community Vulnerability Index (TICV) that uses factors, for example, the quantity of people executed, monetary impacts, and social vulnerability to depict to the dimension of impact a tornado event has on community.